Obesity among children aged 10-13 years in public and private elementary schools - Evi Kamelia; Nurdiani Nurdiani; Tiansa Sembiring; Hakimi Hakimi; Iskandar Z Lubis (Paediatrica Indonesiana, 2003)
Background In the last few years, the prevalence of obesity amongIndonesian children has been beginning to increase slowly, butstudies and publications about obesity are limited. In accordancewith the improvement of social economic and child health, obesitycan be seen more frequently as a problem in children.Objective To evaluate and compare the prevalence and relatedfactors of obesity among children 10-13 year-old who were stu-dents of two kinds of school, namely public and private elementaryschool.Methods A cross sectional study was done from October untilDecember 1995 on 276 elementary school students aged 10-13years consisting of 138 public and 138 private elementary schoolstudents. Data were collected by a questionnaire including anam-nesis of family history and type of daily diet, physical examination,and anthropometric measurement.Results The prevalence of obesity among children in the publicand private elementary schools was 9% and 20% respectively,which showed a significant difference (p<0.01). The prevalence ofobesity among children was significantly related to parents’ wel-fare, excessive daily calorie intake, level of physical activity, andobesity problem in the family.Conclusion The prevalence of obesity in students of private andpublic elementary schools was 20% and 9% respectively. Socialeconomic level, calorie intake, sport activities, and obesity prob-lems in the family are factors related to the prevalence of childobesity